Irradiation-Induced Intestinal Damage Is Recovered by the Indigenous Gut Bacteria Lactobacillus acidophilus - Sittipo, Panida; Pham, Huy Quang; Park, Chang Eon; Kang, Gi-Ung; Zhi, Yong; Ji, Hyun Jung; Jang, Ayeung; Seo, Ho Seong; Shin, Jae-Ho; Lee, Yun Kyung (Frontiers in Cellular and Infection Microbiology, 2020)
The intestinal tract is one of the most sensitive organs following irradiation. The protective effect of specific indigenous microbiota on irradiation-induced damage to intestinal epithelial cell (IEC) has not been reported. Mice were irradiated with a single dose of 6 Gy of gamma rays. The intestinal damage was analyzed by histopathology. Intestinal stemness and differentiation were determined by intestinal organoid culture. Microbiota community was observed by high-throughput 16S rRNA gene sequencing and oligotyping analysis. We showed that distal small intestine was damaged by sublethal dose of gamma irradiation. Intestinal organoids derived from the irradiated mice showed defects in budding and mucin expression, suggesting the detrimental effect of irradiation on the intestinal stemness and differentiation. In addition, irradiation reduced intestinal immunoglobulin A level, concomitant with decreased microbiota diversity based on our high-throughput 16S rRNA gene sequencing data. Especially, the relative abundance of Lactobacillus was reduced at early time point post-irradiation; however, it was recovered at late time point. Oligotyping analysis within the Lactobacillus genus indicated that Lactobacillus-related oligotype 1 (OT1) including Lactobacillus acidophilus might drive recovery after irradiation as it was associated with increased long-term numbers post-exposure. We showed that treatment with heat-killed L. acidophilus rescued the budding-impaired organoids and induced sufficient differentiation in epithelial cells, and particularly mucin-producing cells, in intestinal organoids. This study provides the first evidence that the indigenous gut bacteria L. acidophilus enhance intestinal epithelial function with respect to irradiation-induced intestinal damage by improving intestinal stem cell function and cell differentiation.